(untitled) - Prof Dr. Marko Bachl, Prof. Dr. Christine Lohmeier, Prof. Dr. Helena Stehle, Asst. Prof. Dr. Anna Wagner (SCM Studies in Communication and Media, 2013)
The E-Journal published by the German Communication Association (Deutsche Gesellschaft für Publizistik- und Kommunikationswissenschaft, DGPuK e.V.) aims to present a full range of studies in communications and media on a high level of quality. It therefore seeks to publish new research results in the field of media and communication sciences, gives a general overview of the international state of research and create a forum for interdisciplinary discussions. The journal publishes top blind peer-reviewed  papers in German and English; German contributions will be accompanied by an extended, quotable abstract in English. Website: www.scm.nomos.de